The role of Central Asia in the discovery of global warming - Forêt, Philippe (My University, 2009)
The review of precise field maps and photographs should help me reconstruct not only the environmental and cultural history of Central Asia, but also the scholarly debate on climate that occurred during the first three decades of last century. I will very specifically investigate expedition reports because these publications exemplify the methodological guidelines enforced by the scholarly community. I will indeed argue that Stein's Explorations in Turkestan or Hedin's Sino-Swedish "Scientific Expedition to the North-western Provinces of China" provide a useful framework to analyze the first debate on global warming.
Department of Oriental Languages, Stockholm University
Keywords: role of Central Asia; discovery; global warming; Research Subject Categories::HUMANITIES and RELIGION::Religion/Theology::History of religion